EFFECTS OF VITAMIN E AND SELENIUM ON LEUKOCYTE PROFILE AND REPRODUCETION PERFORMANCE IN AWASSI EWES - Makkawi, A.Aziz; Hamra, Amera; El Abdalla, Saleh Badie (Journal of Veterinary Medicine and Animal Production, 2021)
Thirty Awassi ewes, 3- 3.5 years old with mean body weight of 50 ± 1.27 kg, were divided into three equal groups ( A, B and C). Animals in group A were injected with 100 ml of vitamin E (Vit E) and then 200ml three days later. Animals in group B were injected with 60ml vit E + 2250 microgram of Selenium (Se) followed by 80ml vit E and 3000 microgram Se three days later, group (C) ewes were kept as untreated control. Vit E and Se were given intramuscularly (IM) four weeks before and four weeks after mating. Oestrus was synchronized by sponges impregnated with Progesterone. The total blood leukocyte counts (WBC) and differential white cell counts and packed cell volume (PCV) were determined at the end of the experiment. Data on oestrus synchronization, conception rate, fertility, litter size and lamb birth weight were analyzed.